The place of society and societal issues in the education and training policy of Ethiopia: A content analysis - Mulugeta Yayeh Worku; Solomon Melesse Mengistie; Alemayehu Bishaw Tamiru (College of education, Bahir Dar University, 2023)
Using the Social Reconstructionist educational philosophy as a theoretical framework, this study attempts to understand the place of society and major societal issues in the current Education and Training Policy of Ethiopia. To achieve this purpose, an analysis was made both on the manifest and latent contents of the whole policy document. The analysis revealed that in the present Education and Training Policy of Ethiopia, words, concepts, phrases, sentences, and paragraphs that reflect basic ideas of the Social Reconstructionist educational philosophy were not satisfactorily incorporated. Besides, though some society-related concepts were explored, contents dealing with sensitive social, economic, and political problems were not adequately included. Based on the above findings, therefore, it is concluded that the Education and Training Policy of Ethiopia has not satisfactorily echoed society and major societal issues, particularly those that are given much emphasis in the Social Reconstructionist educational philosophy. Hence, towards the end of the article areas of intervention that could possibly ameliorate this problem are highlighted.